Construction of social innovation indicators - Méndez, Edwin Leonardo; Valenzuela, Silvia Maria (2021)
Social innovation at the national and international level has not been quantitatively measured, due to the lack of information resources collected, since by engaging topics such as quality of life, empowerment, social appropriation of knowledge, sustainability, replicability and scalability in a single concept, it is a bit wasteful to quantify what a social innovation initiative is even more when the entities in charge of this measurement have not done so, leaving the subject of innovation to a single context such as the technological one and leaving aside the Social.